Public Information Transparency Communication Management in Encouraging Accountability in Regional Governance - Novianty Elizabeth Ayuna (SEAN Institute, 2024)
This study aims to analyze communication management in the implementation of public information disclosure as a primary instrument for promoting accountability in regional governance. In the era of digital democracy, transparency is not merely a regulatory obligation stipulated in Law No. 14 of 2008, but rather a strategic communication strategy to build public trust. The research method used was descriptive qualitative with a case study approach. Data were collected through in-depth interviews with Information and Documentation Management Officers (PPID), observations of regional government digital communication channels, and documentation studies of public information access reports. The results indicate that communication management, including planning the Public Information List (DIP) and interactive use of digital platforms, positively contributes to public accountability. However, this study identified structural barriers in the form of sectoral egos between regional government agencies (OPD) and cultural barriers in the form of a closed bureaucratic culture that views information as an instrument of power. The study's conclusions confirm that professionally managed information disclosure can transform accountability from a mere administrative formality to a real public accountability. Successful communication management ultimately strengthens public oversight and ensures the sustainability of regional development through social capital in the form of public trust.